Pushing the limits disabled dykes produce culture - Tremain, Shelley (Women's Press, 2009)
Cet impressionnant recueil de prose, de poésie, de chansons et d'art visuel rédigé par des lesbiennes handicapées est la première de deux anthologies liées (la seconde est un recueil d'essais). Dans son introduction percutante (« Nous sommes ici. Nous sommes handicapés et queer. Habituez-vous-y »), la rédactrice en chef Shelley Tremain appelle à la reconnaissance et à la compréhension du monde selon les lesbiennes handicapées. La collection elle-même est colérique, compatissante, drôle et surtout émouvante. Sherree Clark présente des extraits de son recueil de poésie et d'art Living with Arthritis. Margot K. Lane célèbre la sexualité dans un merveilleux poème intitulé « Full day ». Le récit posthume de Kathleen Martindale sur le cancer du sein est un appel à l’action contre le personnel médical insensible, tout comme la chronique de Kathleen Rockhill sur sa guérison d’un accident de voiture dévastateur. Combinant colère et célébration, Pushing the Limits est une révélation.
Keywords: amériques; anthologie; approches et analyses; arts; canada; capacitisme; corps; lesbianisme; littérature; outils; ouvrages de références; patriarcat; personnes lesbiennes; poésie; queer; racisme; ressource en ligne; régions géographiques; santé; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

From gender bias to gender awareness in medical education - Verdonk, Petra; Benschop, Yvonne W. M.; de Haes, Hanneke C. J. M.; Lagro-Janssen, Toine L. M. (Advances in Health Sciences Education, 2009)
Gender is an essential determinant of health and illness. Gender awareness in doctors contributes to equity and equality in health and aims towards better health for men and women. Nevertheless, gender has largely been ignored in medicine. First, it is stated that medicine was ‘gender blind’ by not considering gender whenever relevant. Secondly, medicine is said to be ‘male biased’ because the largest body of knowledge on health and illness is about men and their health. Thirdly, gender role ideology negatively influences treatment and health outcomes. Finally, gender inequality has been overlooked as a determinant of health and illness. The uptake of gender issues in medical education brings about specific challenges for several reasons. For instance, the political-ideological connotations of gender issues create resistance especially in traditionalists in medical schools. Secondly, it is necessary to clarify which gender issues must be integrated in which domains. Also, some are interdisciplinary issues and as such more difficult to integrate. Finally, schools need assistance with implementation. The integration of psychosocial issues along with biomedical ones in clinical cases, the dissemination of literature and education material, staff education, and efforts towards structural embedding of gender in curricula are determining factors for successful implementation. Gender equity is not a spontaneous process. Medical education provides specific opportunities that may contribute to transformation for medical schools educate future doctors for future patients in future settings. Consequently, future benefits legitimize the integration of gender as a qualitative investment in medical education.
Keywords: approches et analyses; discipline; europe; formation des médecins; médecine; pays-bas; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; sciences; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation